Biografien und Netzwerke im Kaffeehandel zwischen Deutschland und Zentralamerika 1920-1959 - Berth, Christiane (Hamburger Historische Forschungen, 2014)
Coffee is not only a popular drink, but also linked different worlds: The coffee trade linked Hamburg and Bremen to transnational networks between Europe and Latin America.Central America was important for global coffee trade because the region was the first to introduce the "wet" form of treatment. The high quality of these "washed" coffees made them sought-after on the world market. German immigrants shaped the trade links between the Central American coffee-growing regions and the North German port cities: They founded export companies, purchased coffee plantations and participated in the prefinancing of the harvests.Christiane Berth analyses biographies and networks of German coffee actors in Guatemala, Costa Rica and Chiapas. It shows how their trade networks became fragile as a result of economic crises and new foreign policy constellation, how it came under pressure in National Socialism and broke up during the Second World War. Nevertheless, trade relations between nation states, networks in the coffee industry and the biographies of coffee players remained closely interlinked, even in the post-war period.